„The Medici Effect” – Business Models in the International Relations - Vasileva, Evgenia (Research Papers, 2018)
The political and corporate world is becoming increasingly technological, networked and inseparable, which provides and permits interdisciplinary, unlimited and diverse research frameworks and models. This article is an attempt to apply analytical tools from the field of business management and strategic planning for analysis in the field of international relations, diplomacy and everyday policy making. The assumption is that innovation in ideas stems from combining, colliding, merging of existing concepts and cultures and not from hard discipline differentiations.
Keywords: Business; Diplomacy; Interdisciplinary; The medici effect; Innovations; International relations; Strategic management